Membrane dual-targeting probes: A promising strategy for fluorescence-guided prostate cancer surgery and lymph node metastases detection - Ling-Ling Wu; Qinxin Zhao; Qinghua Wang; Qingyang Zhang; Feiya Yang; Bo Zheng; Hai-Yu Hu; Nianzeng Xing (Elsevier, 2023)
Fluorescence-guided surgery (FGS) with tumor-targeted imaging agents, particularly those using the near-infrared wavelength, has emerged as a real-time technique to highlight the tumor location and margins during a surgical procedure. For accurate visualization of prostate cancer (PCa) boundary and lymphatic metastasis, we developed a new approach involving an efficient self-quenched near-infrared fluorescence probe, Cy-KUE-OA, with dual PCa-membrane affinity. Cy-KUE-OA specifically targeted the prostate-specific membrane antigen (PSMA), anchored into the phospholipids of the cell membrane of PCa cells and consequently showed a strong Cy7-de-quenching effect. This dual-membrane-targeting probe allowed us to detect PSMA-expressing PCa cells both in vitro and in vivo and enabled clear visualization of the tumor boundary during fluorescence-guided laparoscopic surgery in PCa mouse models. Furthermore, the high PCa preference of Cy-KUE-OA was confirmed on surgically resected patient specimens of healthy tissues, PCa, and lymph node metastases. Taken together, our results serve as a bridge between preclinical and clinical research in FGS of PCa and lay a solid foundation for further clinical research.